Halal Food on Airplanes in Indonesia: Does it Provide Optimal Information? - Annalisa Yahanan; Sri Turatmiyah; Hamonangan Albariansyah; Febrian Febrian; Nurhidayatuloh Nurhidayatuloh (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2024)
The majority of Indonesia’s population adheres to Islam. Therefore, it is essential that food consumption complies with Islamic law, including food consumed on airplanes. However, the information available to passengers regarding the halal status of food remains unclear. The purpose of this study is to analyze the regulation of halal products in Indonesia and to analyze the right to halal product information provided by Indonesian airlines during flights. The research was conducted normatively using a legislative and conceptual approach. Data on halal food information was obtained through internet searches and the food provided by airlines. The results showed that the regulation of halal products in Indonesia more clearly provides protection to consumers than in the Netherlands. Indonesia requires every food product in circulation and trade to include a halal label, namely the halal logo and halal certificate number without exception, while in the Netherlands this is not the case. In Indonesia, food information with a halal label on the plane, not all of them include it on the packaging of food products even though they already have a halal certificate. Passengers will be more comfortable and confident if the halal label information is easy to find and easy to read either on product packaging or in certain places.